The Effects of Psychological Contracts and Organizational Support on Organizational Commitment Behavior on Millennial Generation Employees - Desi Setya Ngaeni; Iwan (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Employers and business owners who employ Generation Y as their workforce face many challenges along with tech-savvy characteristics, demands and lifestyles that are different from the previous generation. In this context, a strong psychological contract becomes an important antecedent in a company that employs Generation Y. This study seeks to analyze the effect of psychological contracts and organizational support on organizational commitment behavior (OCB) among millennial generation employees, using organizational commitment as a mediating variable. This study used a quantitative approach using simple random sampling technique with a total sample of 176 samples. The analysis technique was carried out using Structural Equation Modeling (SEM) with AMOS software. The findings indicate that organizational support and the psychological contract have a big impact on organizational commitment and OCB. The results show that organizational commitment has a considerable impact on organizational commitment behavior. Examining the organizational commitment's mediating function, the findings indicate that it plays a full mediating function in enhancing the impacts of psychological contracts and organizational support on OCB. Practically, these findings have implications for the importance of employee engagement through organizational commitment which predicts it is more likely to increase employee perceptions of the psychological contract and encourage positive behaviors that promote OCB. Keywords: millennial generations, organizational commitment, organizational commitment behavior (ocb), organizational support, psychological contracts